2021
DOI: 10.1002/csc2.20580
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of effects of trifluoromethanesulfonamide in sorghum inbred lines and their derived hybrids

Abstract: In sorghum [Sorghum bicolor (L.) Moench], development of male‐sterile versions (A‐lines) of the seed parents (B‐lines) is a tedious and time‐consuming process limiting opportunities for the improvement of new seed parents. Assessment of the value of a potential new seed parent requires testcross hybrid evaluations, but because of male fertility of these lines, conventional methods are inadequate to generate hybrid seed required for testing. Mechanisms to reduce the number of lines that require sterilization wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…These populations displayed a range of phenotypic variation for days to mid-anthesis, plant height, and GY. A total of 89 lines from the BTx623/BTx642 population and 128 lines from the BTx623/BTx378 population were male sterilized with TFMSA using methods described in Kyanam et al (2021). Each TFMSA-sterilized line was used as a seed parent with two of four available pollinator lines: R07178, R08306, RTx436, and RTx437.…”
Section: Agronomics and Phenotypic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…These populations displayed a range of phenotypic variation for days to mid-anthesis, plant height, and GY. A total of 89 lines from the BTx623/BTx642 population and 128 lines from the BTx623/BTx378 population were male sterilized with TFMSA using methods described in Kyanam et al (2021). Each TFMSA-sterilized line was used as a seed parent with two of four available pollinator lines: R07178, R08306, RTx436, and RTx437.…”
Section: Agronomics and Phenotypic Datamentioning
confidence: 99%
“…An approach to induce temporal male sterility would permit early generation testing of B-lines in hybrid combination. Hodnett and Rooney (2018) reported that trifluoromethanesulfonamide (TFMSA) effectively induces male sterility in B-lines, and Kyanam et al (2021) further demonstrated its suitability to produce hybrids for yield testing. As such, the male gametocide TFMSA provides an alternative to the use…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loussaert ( 2004 ) reported that application of 200–500 µg of TFMSA per maize plant to the most recent fully expanded leaf effectively induced male sterility irrespective of the time of application. Similarly, Hodnett and Rooney ( 2018 ) and Kyanam et al ( 2021 ) found that 30 mg TFMSA applied 34 days before flag leaf emergence, or 25 mg TFMSA in a split application (15 mg 55 days after planting, followed by 10 mg 9 days later) effectively induced male sterility in sorghum. In this study, the actual amount of the estimated TFMSA stayed on to cowpea at one-time application in IT86D-1010 was 10.4 mg per plant and 11.0 mg in IT97K-499-35.…”
Section: Discussionmentioning
confidence: 88%
“…Among many uses, sorghum is most commonly produced in the United States for grain and forage, primarily used to production relies on the A1 cytoplasmic male sterility system that is based on the A-, B-, and R-line system (Stephens & Holland, 1954 ). Creating A-/B-pairs is time consuming and requires several rounds of backcross, which is the reason that sorghum breeders typically evaluate B-lines in hybrid combinations via A3 R lines or trifluoromethanesulfonamide prior to A-line creation (Kyanam et al, 2021;Lee et al, 1992 ). Selection of any new parental lines is evaluated primarily on the performance of hybrids produced with those parents.…”
Section: Introductionmentioning
confidence: 99%